Pengaruh Gaya Kepemimpinan Islami, Budaya Organisasi Islami dan Insentif terhadap Produktivitas Kerja Karyawan PT Yanmar Indonesia - Muhamad Ekhsan; Roni Mariyono (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2020)
This study aims to examine whether there is an influence of Islamic leadership style, Islamic organizational culture and incentives to the work productivity of PT. Yanmar Indonesia. The population in this study were employees who worked with PT Yanmar Indonesia section totaling 97. The sampling method used was nonprobability sampling, namely the saturated sampling method. This research uses the SPSS program. The results of this study prove that there is a positive and significant influence between Islamic leadership style and work productivity, there is a positive and significant influence between Islamic organizational culture and work productivity, there is a positive and significant effect between incentives and work productivity.